Mathematics Education and the Engineering Students - Singh, B. B. (Journal of Engineering Education Transformations, 1999)
Mathematics is the mother of all sciences. Without Mathematics, we can not think of the existence of engineering sciences even. Therefor, our modern. civilization which is entirely the outcome of science and technology has got a very close touch with mathematical education.